Determining the Informatics and Conceptual DFT Study of Pigments Derived from Carotenoids of Marine Origin - Flores-Holguin, Norma; Frau, Juan; Glossman-Mitnik, Daniel (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
The objective of this work was to assess the behavior of five density functionals, CAM-B3LYP, LC- \(ω\)HPBE, MN12SX, N12SX and \(ω\)B97XD, in connection with the Def2TZVP basis set and the SMD solvation model for the calculation of the molecular properties, chemical reactivities and solubilities of some pigments derived from the Astaxanthin, \(β\)-Cryptoxanthin, Fucoxanthin, Myxol, Siphonaxanthin, Siphonein and Zeaxanthin marine carotenoids in the presence of different solvents (hexane, methanol, ethanol and water). All the chemical reactivity descriptors for the systems were calculated via Conceptual Density Functional Theory (CDFT). Finally, the potential bioavailability and druggability as well as the bioactivity scores for the marine carotenoid pigments were predicted through different methodologies already reported in the literature which have been previously validated during the study of other natural products obtained from marine sources.